Central venous catheter-related blood stream infections in neonatal care unit - Badr, Rawia Ibrahim; Hammad, Enas; Salama, Mona Foda; Shouman, Basma; Abdel-Hady, Hesham; Nasef, Nehad (International Journal of Infection Control, 2013)
Objective: The aim of this study was to detect the rate of catheter-related bloodstream infection (CRBSI) in NICU of Mansoura University Children's Hospital and to focus on possible predictors of infection. Study Design: A cross sectional comparative study to detect rate of CRBSI among neonates with central vascular catheters during the period between January 2009 and April 2012. Then, a nested case control study done among CRBSI cases and central vascular catheters none infected as a control group to detect predictors associated with their occurrence. Patients and Methods: Blood samples were collected from 111 neonates clinically suspected of septicemia and had inserted venous line. Central, peripheral blood and catheter tip cultures were done for each case. Results: CRBSI was confirmed in 69 cases as central blood culture count was ˃ 3 folds of peripheral blood culture count. Catheter tip culture showed ˃ 103 CFU/ ml per catheter of the same organisms. Low birth weight, age below 7 days, prematurity, mechanical ventilation, TPN administration and prolonged hospital stay were predictors of CRBSI. Logistic regression of the studied predictors showed that birth weight, TPN administration and length of central venous catheter stay were significant predictors of CRBSI. Conclusion: CRBSI is a common problem in NICU. Predictors of CRBSI included low birth weight, prematurity and mechanical ventilation. Potential use of TPN, prolonged catheter stay and low birth weight are independent predictors for CRBSI.